Overexpression of CYP11A1 recovers cell cycle distribution in renal cell carcinoma Caki-1 - HIEN THI MY ONG; Kim, Tae-Hun; EDA ATES; Pyun, Jae-Chul; Kang, Min-Jung (BioMed Central, 2022)
Background Clear cell renal carcinoma is commonly known for its metastasis propensity to outspread to other organs and is asymptomatic in the early stage. Recent studies have shown that deficiencies in CYP11A1 expression can lead to fatal adrenal failure if left untreated and are associated with downstream regulation in various cancer types. However, the molecular mechanisms of CYP11A1 and kidney cancer proliferation remain unclear. Methods Normal and renal carcinoma cell lines (HEK293 and Caki-1) were transfected with plasmid encoding CYP11A1 to overexpress the P450scc protein. Cell cycle distribution was investigated using flow cytometry. The expression of proteins related to C-Raf/ERK/JNK/p38 signaling pathways was examined using western blot. Results We observed that CYP11A1 overexpression suppressed the cyclin B1 and cell-division cycle 2 expression while cyclin-dependent kinases 2 and 4 were unaffected. Cancer cell migration and invasion were suppressed along with epithelial-intermediate metastatic markers Snail and Vimentin. In addition, in CYP11A1-overexpressing Caki-1 cells, cdc2/cyclinB1 was downregulated while the phosphorylation of cdc25c, a G2/M arrest-related upstream signal, was increased. The intrinsic-mitochondrial apoptosis markers were not significantly altered. We also identified that the C-Raf/ERK/JNK/p38 pathway is an important pro-apoptotic mechanism in CYP11A1-overexpressing cell-based models. Our results suggest that CYP11A1 overexpression recovered the disturbed cell cycle arrest distribution in renal carcinoma cell line Caki-1 through G2/M arrest and C-Raf/ERK/JNK pathway. Conclusions Our findings may suggest promising new therapeutic targets to suppress kidney cancer proliferation without affecting normal cells, eventually improving the survival of patients with cancer.